2005
DOI: 10.1182/blood-2004-09-3507
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells express a restricted set of functionally active chemokine receptors capable of promoting migration to pancreatic islets

Abstract: IntroductionBone marrow (BM) is a complex tissue containing hematopoietic progenitor cells and a connective-tissue network of stromal cells. Marrow stroma includes a subpopulation of undifferentiated cells that are capable of becoming one of a number of phenotypes, including bone and cartilage, tendon, muscle, fat, and marrow stromal connective tissue that supports hematopoietic cell differentiation. 1,2 These cells are referred to as mesenchymal stem cells (MSCs), since they are known to have capacity of prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
365
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(384 citation statements)
references
References 57 publications
14
365
2
3
Order By: Relevance
“…Future studies will focus on identification of factors produced by the injured pancreas. In addition, it will be important to characterise the response of putative adult beta stem cell types, such as bone marrow-derived mesenchymal stem cells [26] and intra-pancreatic stem cells [27,28], to stimuli produced by the STZ-injured pancreas. This may be a valuable system for understanding the mechanisms of beta cell neogenesis in the adult and for identification of regenerative factors for use in tissue engineering in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will focus on identification of factors produced by the injured pancreas. In addition, it will be important to characterise the response of putative adult beta stem cell types, such as bone marrow-derived mesenchymal stem cells [26] and intra-pancreatic stem cells [27,28], to stimuli produced by the STZ-injured pancreas. This may be a valuable system for understanding the mechanisms of beta cell neogenesis in the adult and for identification of regenerative factors for use in tissue engineering in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 In recent years, special attention has been drawn to chemokines that stimulate the migration of human bone marrow-derived mesenchymal stem cells. 12,28,29 CSP that were used in the present study are actively recruited by PRP as shown here and by human synovial fluid containing the chemokines CCL25, CXCL10, and XCL1 that stimulate CSP migration in 96-well chemotaxis assays. 21,30 Therefore, it is most likely that PRP, respectively its particular growth factors and chemokines independently or synergistically may enhance the migration of human subchondral progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…MSC can also produce a variety of growth factors, cytokines, chemokines and proteases that are likely to play a role either in their immunomodulatory or in their migratory function [29][30][31]. In this respect, MSC have been shown to express a restricted pattern of chemokine receptors, including CXCR4, allowing them to migrate to tissues upon specific chemotactic triggers [32][33][34][35]. These features are likely to represent the basis for MSC homing to multiple organs where they undergo a program of tissue-specific differentiation [36].…”
Section: Immunological Phenotype and Functions Of Mscmentioning
confidence: 99%